Spin Coating technique for obtaining nanometric thin films in the system La0.7Sr0.3MnO3 - Mera-Córdoba, Jenny Alejandra; Mera-Córdoba, María Angélica; Córdoba-Barahona, Carlos Arturo (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Manganite in the La0.7Sr0.3MnO3 system is of great interest due to its potential application in fuel cells, information storage, magnetic field sensors, non-volatile memories, oxygen sensors, and catalysts in the oxidation of light hydrocarbons. Given the scientific relevance of this material, this study describes the procedure to synthesize and characterize thin films of La0.7Sr0.3MnO3. Manganites were synthesized by means of the Pechini method, and deposited on strontium titanate substrates using spin-coating. Both the crystallinity of the films and their phases were studied with X-ray diffraction (XRD), finding that the films are polycrystalline and have a simple cubic structure with a lattice constant a=3.8653 ± 0.066 Ǻ. Scanning electron microscopy (SEM) showed a uniform surface with good morphological features, and the spectrum resulted from the Energy Dispersive X-Ray Spectroscopy (EDS) analysis over the same film was consistent with the molar ratio of the perovskite. Samples of 2, 4, and 6 layers were synthesized, obtaining thicknesses of 75.10 ± 0.01, 75.02 ± 0.01 and 74.07 ± 0.08 nm per monolayer. The results indicate that this method is useful to synthesize films of high crystalline quality and nanometric size.